MORPHOLOGICAL ASPECTS OF PANCREAS CHANGES IN EXPERIMENTAL HYPOTHYROIDISM - Niyozov, N.K.; Akhmedova, S.M.; Usmanov, R.D.; Mirsharopov, U.M.; Nisanbayeva, A.U. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Background. Hypothyroidism is associated with several disorders in all organs and systems due to the various effects of thyroid hormones. First of all, the circulatory system, the digestive system (liver function), the central nervous system, the organs of vision, and the reproductive system are affected. Methods. Research has scientifically substantiated the results of inspections conducted on 56 white laboratory rats during early postnatal ontogenesis. In the complex morphological studies, which include in its membership general histologic, histochemical techniques organometal, and morphometry. Experiments and slaughter of animals were carried out by the “European Convention for the Protection of Vertebrate Animals used for Experimental and other Scientific Purposes”. Conclusion. For the study, we used the offspring of rats born from control and experimental white laboratory rats - mothers under conditions of hypothyroidism. The results of the study showed that the introduction of Mercazolil into the pancreatic lobules of experimental rats led to changes associated with the normalization of the structural organization of the pancreatic cranium, interlobular connective tissue with the formation of fibrous tissue components, as well as the disappearance of choroidal oedema observed in the interlobular connective tissue.